The Novel as an Interpretation of Life - Khadka, Kabita (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2023)
The novel presents and captures the remarkable moments of human life presenting its different aspects even if it is called fiction. A novel, in this regard, interprets life in the form of plot, characters, costumes, and through many more things. This research paper aims at investigating how novels interpret human life through their presentation of characters, plot, language, design and the narratives centered on human societies. For this, the study has employed qualitative methodology, and data in the study were brought from secondary sources. Those secondary sources included different journal articles, books, novels, and other publications related to the novel as a literary genre. The major finding of the present study includes that novel has the specific power to portray different ups and downs of human life; it is an interpretation of human life; the novel works as a discourse of life; and it recaptures the spirit of time through different incidents.